(untitled) (Texas Journal of Medical Science, 2023)
Diabetes mellitus and its complications remain an urgent problem of modern surgery. Therefore, it is important for surgeons to create new stages in the treatment of diabetic foot syndrome and restore their ability to work and improve the quality of life in relation to patients. An assessment of the effectiveness of a new biological preparation is shown